(من بعض أسرار التشبيه في القرآن الكريم (دراسة تحليلية حول الأيات التربوية - Fuadi, Afif (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2019)
The researh is aimed to analyze the studies about meaning of abstrat parable in Al-Quran. The important of this has relation to eduation verse. The point problem of this research was education verse about abstract parable in Al-Quran.The research was a library studies. It was desriptive research which used qualitative approach. The researcher collected the data from references of balakhoh book, tafsir, ilmualquran, ilmuhadis et all. The result of this research was the researcher saw that parable has good position in balakhohstudiesandeduation. Many verse of A-lQuran which exist in it from models (kinds of language used) and verse abstract.The conclusions of this research were:1.describing the condition of parable thing (تقرير حال المشبه), 2.reinforcing the condition of parable thing (تأكيد حال المشبه) , 3. Beautifying the condition of parable thing (تزيين حال المشبه)and, 4. making worse the condition of the parable thing (تقبيح حال المشبه)